2020
DOI: 10.1061/(asce)co.1943-7862.0001884
|View full text |Cite
|
Sign up to set email alerts
|

Eye-Tracking Experimental Study Investigating the Influence Factors of Construction Safety Hazard Recognition

Abstract: Full bibliographic details must be given when referring to, or quoting from full items including the author's name, the title of the work, publication details where relevant (place, publisher, date), pagination, and for theses or dissertations the awarding institution, the degree type awarded, and the date of the award.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 50 publications
(74 reference statements)
0
37
1
Order By: Relevance
“…Yet, another study from the United Kingdom found that individuals may fail to recognize up to 33% of relevant safety hazards [14]. Similar and more recent replications have also reinforced these previous findings in the context of nations including Asia, the Middle East, and other geographical regions [12][13][14][15][16][17][18]20,27].…”
Section: Significance Of Construction Hazard Recognitionmentioning
confidence: 52%
See 2 more Smart Citations
“…Yet, another study from the United Kingdom found that individuals may fail to recognize up to 33% of relevant safety hazards [14]. Similar and more recent replications have also reinforced these previous findings in the context of nations including Asia, the Middle East, and other geographical regions [12][13][14][15][16][17][18]20,27].…”
Section: Significance Of Construction Hazard Recognitionmentioning
confidence: 52%
“…Moreover, such an investigation can offer important insights into problem areas and challenges that workers experience as they participate in hazard recognition efforts-for which robust solutions will need to be developed. Unlike previous efforts that examined the effect of factors such as safety climate [45], worker experience [17], and other factors [16,43] on hazard recognition levels and related safety outcomes [45], the current investigation examined if workers demonstrate any disparities in recognizing hazards of different types or categories.…”
Section: Research Objectives and Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Visual behaviors have been studied in cognitive neuroscience, computer science, consumer science, environmental design, and psychophysiology (Epelboim and Suppes, 2001;Andrá et al, 2015;Muldner and Burleston, 2015). Although eyetracking is not a direct measure of visual acuity, it has been used as a useful tool in research and applications, such as usability research (Manhartsberger and Zellhofer, 2005), human factors research, and safety applications (Han et al, 2020), psychological/cognitive research (Mele and Federici, 2012), education and training (Tien et al, 2014), kinesiology and sports sciences (Lim et al, 2018), and car/airplane simulations (Palinko et al, 2010). However, a generally agreed limitation with eyetracking data is that while these data can explain overt attention, i.e., what is observed and perceived, they do not contribute to understanding the covert, such as why and how.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical practitioners and researchers are therefore increasingly turning to eye tracking to provide insight into the psychological mechanisms underpinning various clinical disorders, such as depression, autism and a range of anxiety disorders [2]. Eye tracking is also gaining greater interest in applied fields including sports [3,4], medical sciences [5,6], the military and law enforcement [7], aviation [8], driving [9] and civil engineering/hazard recognition [10,11]. However, unlike observations made in more reductionist tasks (e.g., the presentation of threatening/affective versus neutral words) -where outcome measures (and the corresponding underlying mechanisms they represent) are well-established [2] there are inherent difficulties of using eye-tracking to infer specific psychological processes in dynamic and complex (i.e., applied and ecologically valid) tasks.…”
Section: Introductionmentioning
confidence: 99%